Parathyroid cryopreservation following parathyroidectomy: a worthwhile practice? - Shepet, Kevin (2013)
BACKGROUND: Parathyroid cryopreservation is often utilized for patients having parathyroidectomy. This allows for future autotransplantation if a patient becomes permanently hypocalcemic after surgery. However, the practice of cryopreservation is costly and time consuming, while the success rate of delayed autotransplantation is highly variable. We sought to determine the rate and outcomes of parathyroid cryopreservation and delayed autotransplantation at our institution to further evaluate its utility. METHODS: At our institution, 2,083 parathyroidectomies for hyperparathyroidism (HPT) were performed from 2001–2010. Of these, parathyroid cryopreservation was utilized in 442 patients (21%). Patient demographics, preoperative diagnoses, and other characteristics were analyzed, as well as the rate and success of delayed autotransplantation. RESULTS: Of the 442 patients with cryopreservation, the mean age was 55 ± 1 years and 313 (70.8%) were female. 308 (70%) had primary HPT, 46 (10%) had secondary HPT, and 88 (20%) had tertiary HPT. Delayed autotransplantation of cryopreserved parathyroid tissue was used in 4 (1%) patients at an average time of 9 ± 4 months after initial surgery. 3 out of the 4 patients remained hypoparathyroid following this procedure. The one cured patient underwent the procedure only 4 days following the initial parathyroidectomy. CONCLUSION: While cryopreservation was used in over 1/5 of patients undergoing parathyroidectomy, the need for parathyroid reimplantation was very low (1%). Furthermore, the success rate of parathyroid autotransplantation was poor in these patients. Therefore, the continued practice of parathyroid cryopreservation is questionable.